Polemical encounters: Christians, Jews, and Muslims in Iberia and beyond - García-Arenal, Mercedes; Wiegers, Gerard Albert (Iberian encounter and exchange, 2019)
"A collection of essays exploring the polemical encounters in the fields of religion and culture that took place among Jews, Christians, and Muslims in the Iberian Peninsula between the late Middle Ages and the seventeenth century"--Provided by publisher